Parent in Prison: Understanding the Child’s Needs in Educational Institutions - Dadić, Katarina; Horvat, Martina; Mikulić, Una Matea (Acta Paedagogica Vilnensia, 2023)
The departure of a parent to serve a sentence of imprisonment affects the change of a family’s climate, which can be divided into three groups: (a) changes in daily life navigation and activity; (b) changes in parent-child relationships; and (c) changes in financial circumstances. The abrupt change that a child experiences can lead to the development of externalized and internalized behavioral problems, as well as changes in student academic achievement due to lack of motivation and concentration. Since the school is an educational institution that provides children with secondary socialization opportunities, it has an important role in supporting students whose parents are serving prison sentences. This paper presents research suggesting that stigmatizing students whose parents are in prison can bring shame, discomfort, and withdrawal to themselves. Considering that there are no clear suggestions on how the primary school should act when the parent goes to prison, the authors of this paper propose guidelines on minimizing the harmful consequences on socioemotional development and academic success of students whose parents go to prison.
Keywords: child; imprisonment; parenting; school success; stigma